THE PHANTOM STUDY OF SPATIAL REGISTRATION IN PET/CT - NARAWONG, Taratip; YOSHIKAWA, Kyosan; SAGOU, Kenji; TAMURA, Katsumi; ISHIKAWA, Hiroyuki; KANDATSU, Susumu; SUZUKI, Kazutoshi; TANADA, Shuji; SASAKI, Yasuhito; TSUJII, Hirohiko (The ASEAN Journal of Radiology, 2023)
Objective: The purpose of this study was to evaluate the spatial registration in terms of the registration difference in PET/CT with the phantom. Method: Three experiments were performed by using the phantom insert with hollow spheres filled with F-18 and the combined PET/CT system (Siemens, Biograph), including the same offset correction (test 1,2,3) and varied offset correction for the gantry (offset 1,2,3), and the clinical setting. The location of the center of was used for statistical analysis of the location difference. A p-value less than 0.05 was defined to be statistically significant. The acceptable value for the registration difference in the registered image was taken as 1 mm or less. Result: The mean registration difference in the study of same offset correction for the gantry was 0.68±0.24 mm. The p-values obtained in the first experiment were more than 0.05. There was no statistically significant difference between each test. The average registration difference in the study of varied offset correction for the gantry was 0.51±0.17 mm. There was a statistically significant difference when the difference in the z-axis was more than 0.05 mm. The average registration difference in the clinical setting was 0.50±0.28 mm. There was no statistical significance between the clinical setting and the phantom setting.(p-value = 0.764) Conclusion: Inthis PET/CT system, the spatial registration was sufficiently accurate in the phantom study and the spatial registration difference in the registered image was less than Imm.